Amelioration of Seminal Plasma Testosterone Concentration in Gembrong Goats after In Vivo Administration of PGF2α - Hafizuddin, Hafizuddin; Husnurrizal, Husnurrizal; Siregar, Tongku Nizwan; Eriani, Kartini; Wahyuni, Sri; Ahsan, Muhammad Maulana; Sutriana, Amalia; Anwar, Anwar; Aliza, Dwinna (Jurnal Medik Veteriner, 2023)
The semen quality of Gembrong goats is lower than other goats and may be related to the low concentration of testosterone hormone. Implementation of reproductive technology using prostaglandin F2α (PGF2α) hormone is beneficial to increase the testosterone hormone in Gembrong goats. This study aimed to determine the effect of PGF2α injection on increasing testosterone levels in Gembrong goats. Male Gembrong goats (n=4), aged 2.5-4 years with similar body condition scores (BCS=3) were used in this study. Goats were divided into two treatment groups (n=2). Goats in group 1 (G1) were injected intramuscularly with 1 ml PGF2α (75 Î¼g), while those in group 2 (G2) were injected with 1 ml physiological NaCl. Semen collection was carried out 30 minutes after treatment using an artificial vagina. Testosterone levels were measured using the enzyme-linked immunosorbent assay (ELISA). The collected data was tabulated and analyzed descriptively. The results showed that the average testosterone concentration of G1 was higher than G2 with respective concentrations of 6.41 ± 0.70 and 2.81 ± 1.75 ng/ml. It was concluded that administration of PGF2α in vivo could increase testosterone concentration in Gembrong goats.